الوساوس والأفعال القهرية وعلاقتها بالتوافق النفسي لدى طلبة الجامعات في سلطنة عمان - يوسف بن سيف بن محمد الرجيبي
This current study attempts to investigate the possible relationships between obsessions and compulsive acts on one hand and psychological compatibility among students at selected universities in the Sultanate of Oman on the other hand. It also aimed to study the differences between obsessive thoughts, compulsive acts, and psychological compatibility, across participants’ demographic variables, by examining the extent to of these mental illnesses as being affected by personal variables. The study sample consisted of 1007 students from the selected Omani universities, namely Sultan Qaboos University, Sohar University, and the University of Nizwa, using a simple random sampling technique. This technique was used to give each participant equal opportunity and have an equal sample representative in the study. The researcher constructed the instrument based on the literature review due to the lack of a valid instrument that precisely measure what he intended to measure. The psychometric properties of the instrument were validated via experts’ comments while the internal consistencies were examined through Cronbach’s alpha. The results of the internal consistency suggested that the instruments were appropriate and suitable for any academic exercises since the values of Cronbach’s alpha for individual factors ranged between .82 to .93, while its value for individual items ranged between .80 to .93 which indicated appropriateness and suitability of the instruments. Several statistical methods were used to analyze the collected data, such as Exploratory Factor Analysis (EFA), Multiple Linear Regression, and Multivariance Analysis of variance (MANOVA). The EFA was used to summarize the individual items into their latent variable and to investigate the construct validity of the instrument. Moreover, Multiple Linear Regression was utilized to study the potential relationships among the constructs of the study, while MANOVA was used to examine the relationship between obsessive, compulsive actions and psychological compatibility across sample demographic variables. The results of EFA suggested that the Obsessive, Compulsive Acts and Psychological were loaded according to the predetermined theory which indicated strong construct validity. Furthermore, the Multiple Linear Regression analysis found a statistically significant and negative relationship between obsessions and compulsive acts on one hand, and psychological compatibility on the other hand, which indicated the higher the level of obsessive and compulsive acts among the selected subjects, the lower their psychological compatibility would be. The results of the analysis also showed that there were statistically significant differences between the obsessive acts across gender, while obsessive acts were statistically insignificant across university variables. Additionally, the analysis also found compulsive acts were statistically insignificant across gender and university variables respectively.